Улучшение бизнес-процессов детского сада - Чирва, Ангелина Сергеевна (Инноватика - 2017 : сборник материалов XIII Международной школы-конференции студентов, аспирантов и молодых ученых, 20-22 апреля 2017 г., г. Томск, Россия)
The article presents the development of a model in the eTOM (Enhanced Telecom Operational Map) notation of the activity of the kindergarten "Zhanbalazhan". Processes are considered that will help improve the organization's activities. A range of new services for the children's garden is available that will be of direct interest to children.